2001
DOI: 10.1111/j.1748-8583.2001.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Teamworking: a new dynamic in the pursuit of management control

Abstract: This article examines the introduction of teamworking in the pharmaceutical industry. It was found that the organisation of work contained a mix of benefits and costs. The balance between the two was not random; employees' response was influenced by and connected to prior experiences and expectations, management's business strategies and approach to industrial relations and HRM. The article argues that there was a new dynamic, but one cast within the familiar terrain of management seeking to maintain control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 37 publications
4
42
0
Order By: Relevance
“…In these circumstances, together with a high level of job security, worker cohesion did not lead to restrictivism, even though it did not lead to high levels of trust either. This interpretation is supported by the very similar results from a study of a pharmaceuticals plant in Ireland (Geary and Dobbins 2001).…”
Section: Social Relations Of Productionsupporting
confidence: 62%
“…In these circumstances, together with a high level of job security, worker cohesion did not lead to restrictivism, even though it did not lead to high levels of trust either. This interpretation is supported by the very similar results from a study of a pharmaceuticals plant in Ireland (Geary and Dobbins 2001).…”
Section: Social Relations Of Productionsupporting
confidence: 62%
“…Research in the US has shown that certain practices, such as team-working, quality circles and employee involvement, have been used to undermine support for trade unions and to control workers' attitudes and behaviour (Grenier 1988, Clawson andClawson 1999). Although team-working may be a positive experience for some, there are also many examples of where the introduction of teams has led to work intensification and more intense forms of control, particularly in the form of peer pressure (Delbridge and Turnbull 1992, Cappelli et al 1997, Geary and Dobbins 2001. The way that these 'new' forms of work organization are implemented can, therefore, mean that there is little requirement either for critical thinkers or lifelong learners.…”
Section: Downloaded By [Universite Laval] At 19:37 07 October 2014mentioning
confidence: 96%
“…The social, horizontal dimension receives much interest also in several other research streams, including entrepreneurship (Indre and Mark, 2006) and human resource management (e.g., Geary and Dobbins, 2001). 4…”
mentioning
confidence: 99%